NUSANTARA IN FRONT OF MAKASSAR STRAIT: A REVIEW OF INTERNATIONAL LAW OF THE SEA - Judhariksawan Judhariksawan; Aidir Amin Daud; Edmondus Sadesto Tandungan (The Republic of Indonesia Defense University, 2022)
Relocation of the national capital of Indonesia to the Borneo region is not only fraught with considerations of the socio-economic, political, and physical environment. The safety factor is also a very important aspect because the capital city is the center of gravity of the country. Nusantara, the new capital city, directly faces the Makassar Strait which has been designated as an archipelagic sea lane. An archipelagic sea lane must be subject to the international law of the sea, especially the United Nations Convention on the Law of the Sea (UNCLOS) 1982. Foreign voyages and flights have the right of normal mode and continuous passage through archipelagic sea lanes. Therefore, they cannot be blocked. The right of passage is not only granted to merchant ships but also to military ships and even submarines. The extent of the security threat to the capital due to the abovementioned legal regime is analyzed by normative legal research, using a conceptual approach to the legal norms governing the sea lane. This study aims to provide an overview of the legal norms that apply to the Makassar Strait as a consideration in developing a defense and security strategy for the national capital, the archipelago. In conclusion, Nusantara in the Makassar Strait must pay attention to the international law of the sea norms in preparing the defense and security strategy for the new national capital city.